Developing a real time load frequency control for power systems in a real time digital simulator - Tan, Shi Jie (2018)
Maintaining the nominal system frequency is a critical aspect of ensuring stable power system operation in power system stability. During faults or other disturbances, there may be a mismatch between the generation and load in the system. This can cause the system frequency to deviate and decline sharply. This results in a system collapse where there is a loss of electricity supply to the consumers. Under Frequency Load Shedding (UFLS) is one of the techniques employed by system operators to handle this contingency. In UFLS, a certain amount of electrical load is shed to correct the frequency deviation. However, to develop, test and implement the UFLS scheme on a power system, extensive hours and intensive resources are required. Additional costs and time may be required to revalidate the controllers if errors are not rectified during the development phase. Therefore, to speed up the development and testing process, researchers can leverage on real-time simulation technology. In this project, an UFLS scheme was developed and tested on an IEEE 9-bus network on a real-time digital simulator (manufactured by OPAL-RT). Results from the developed UFLS scheme showed the efficacy of the algorithm and demonstrated the benefits of using the powerful computational capabilities of real-time digital simulators in power system stability studies.